Assessment of MC1R and α-MSH gene sequences in Iranian vitiligo patients - Eskandani M; Hasannia S; Vandghanooni S; Pirooznia N; Golchai J (Wolters Kluwer Medknow Publications, 2010)
Background: Vitiligo is an acquired pigmentary disorder of the skin that is caused by unknown factors and is characterized by white and depigmented patches that enlarge and become more numerous with time. Genetic factors, oxidative stress, autoimmunity, and neurochemical agents, such as catecholamines might also contribute to vitiligo. Cutaneous pigmentation is determined by the amounts of eumelanin and pheomelanin synthesized by the epidermal melanocytes and interference of melanocortin-1 receptor (MC1R), a G-protein coupled receptor, its normal agonist, alpha-melanocyte stimulating hormone (α-MSH), and key enzymes, such as tyrosinase, to protect against sun-induced DNA damage. The MC1R, a 7 pass trans-membrane G-protein coupled receptor, is a key control point in melanogenesis. Loss-of-function mutations at the MC1R are associated with a switch from eumelanin to pheomelanin production, resulting in a red or yellow coat color. Aim: In this research, we aim to examine the genetic variety of MC1R and α-MSH gene in 20 Iranian vitiligo patients and 20 healthy controls. Materials and Methods: Analysis of the MC1R coding gene was performed with direct sequencing. Results: We found the following 9 MC1R coding region variants: Arg163Gl (G488A), Arg227Leu (G680A), Val 97Phe (G289T), Asp184Asn (G550A), Arg227Lys (G680A), Arg142His (G425A), Val60Leu (G178T), Val247Met (C739A), and Val174Ile (G520A). We also found 2 frameshift changes: one of them was the Insertion of C (frameshift in Pro136, stop at Trp148) and the other, Insertion of G (frameshift in Pro256, stop at Trp 333). Of all the changes, the most common was Val60Leu at 5% in patients vs 20% in controls, Val247Met at 15% in patients vs 0% in controls and Val174Ile at 15% in controls and 0% in patients. The other variants showed a frequency <5% in both patients and controls. Also in this study, we have examined the frequency of single nucleotide polymorphisms within the α-MSH genes with direct sequencing in 20 patients and 20 healthy subjects but found no changes along this gene. Conclusion: We could not find any relationship between MC1R and α-MSH genes and their effect on the disease in Iranian vitiligo patients.